Microsoft Windows server 2003 administrator's pocket consultant - Stanek, William R. (Microsoft Press, 2006)
Here's the practical, pocket-sized reference for IT professionals supporting Microsoft Windows Server 2003 - fully updated for Service Pack 1 and Release 2. Designed for quick referencing, this portable guide covers all the essentials for performing everyday system administration tasks. Topics include managing workstations and servers, using Microsoft Active Directory® directory service, creating and administering user and group accounts, managing files and directories, data security and auditing, data back-up and recovery, network administration using TCP/IP, WINS, and DNS, and more.